Typical Speech Dysfluencies in Fluent Children from Santiago, Chile; [Disfluencias Típicas del Habla en Niños Fluentes de Santiago de Chile] - Roman-Montes de Oca, D (Universidad de Chile, Departamento de Fonoaudiologia, 2020)
The study of fluency of speech, at different stages of the life cycle, is relevant in that it contributes both to the understanding of typical speech development and to the understanding of pathological speech, which is useful for diagnosis and treatment. The objectives of this work are a) to determine the presence and distribution of the disfluencies present in different age groups and b) to determine if there is variation in the distribution of disfluencies in relation to the gender of the informants. The sample consisted of 60 children and adolescents between 4.01 years old and 15.0 years old distributed in three groups. The results indicate that vowel prolongation was the most frequent disfluency, while syllable repetition was the least present in the groups analyzed. In the group of younger women, there was a significantly high amount of word repetition when comparing the presence of this disfluency in the other two groups. There were no more differences reported in relation to the gender of the informants. Finally, the results and some considerations related to the methodology in this type of research are discussed. © 2020, Universidad de Chile, Departamento de Fonoaudiologia. All rights reserved.